Potentiation of glycine-gated NR1/NR3A NMDA receptors relieves Ca2+-dependent outward rectification - Madry, Christian; Betz, Heinrich; Geiger, Jörg; Laube, Bodo (Frontiers in Molecular Neuroscience, 2010)
Glycine has diverse functions within the mammalian central nervous system. It inhibits postsynaptic neurons via strychnine-sensitive glycine receptors (GlyRs) and enhances neuronal excitation through co-activation of N-methyl-D-aspartate (NMDA) receptors. Classical Ca2+-permeable NMDA receptors are composed of glycine-binding NR1 and glutamate-binding NR2 subunits, and hence require both glutamate and glycine for efficient activation. In contrast, recombinant receptors composed of NR1 and the glycine binding NR3A and/or NR3B subunits lack glutamate binding sites and can be activated by glycine alone. Therefore these receptors are also named "excitatory glycine receptors". Co-application of antagonists of the NR1 glycine-binding site or of the divalent cation Zn2+ markedly enhances the glycine responses of these receptors. To gain further insight into the properties of these glycine-gated NMDA receptors, we investigated their current-voltage (I-V) dependence. Whole-cell current-voltage relations of glycine currents recorded from NR1/NR3B and NR1/NR3A/NR3B expressing oocytes were found to be linear under our recording conditions. In contrast, NR1/NR3A receptors displayed a strong outwardly rectifying I-V relation. Interestingly, the voltage-dependent inward current block was abolished in the presence of NR1 antagonists, Zn2+ or a combination of both. Further analysis revealed that Ca2+ (1.8 mM) present in our recording solutions was responsible for the voltage-dependent inhibition of ion flux through NR1/NR3A receptors. Since physiological concentrations of the divalent cation Mg2+ did not affect the I-V dependence, our data suggest that relief of the voltage-dependent Ca2+ block of NR1/NR3A receptors by Zn2+ may be important for the regulation of excitatory glycinergic transmission, according to the Mg2+-block of conventional NR1/NR2 NMDA receptors.